Peran Guru Dalam Membentuk Karakter Positif Anak Usia 5-6 Tahun Di Paud Twi Dini Kota Bengkulu - Wahyuni, Neni Tri; Margaretha, Lydia; Asnawati, Asnawati (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
The purpose of this study was to determine the role of teachers in forming positive characters in early childhood aged 5-6 years in PAUD TWI Dini. Positive characters in early childhood are very important as the basis for forming their personalities in the future. Teachers have a central role in providing direction and good examples, as well as creating an environment that supports the development of children's characters. This study uses a qualitative approach with a case study method. Data were collected through observation, interviews with teachers and documentation. The results showed that teachers in PAUD TWI Dini play an active role in teaching moral, social, and emotional values ​​through various activities, such as educational games, storytelling, and social activities that involve cooperation between children. In addition, teachers also provide good role models in everyday life. Another factor that supports the formation of positive characters in children is the involvement of parents who work together with teachers in maintaining child development. This study concludes that the role of teachers is very significant in forming positive characters in early childhood through a holistic and collaborative approach between teachers, children, and parents.